ANALISIS KEMAMPUAN KOGNITIF DAN MINAT BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING MATERI ENERGI ALTERNATIF KELAS X SMA MUHAMMADIYAH LIMBORO SERAM BAGIAN BARAT - Madiisa, Eriyanti; Elsina S.Tamaela; Asry. N. Latupeirissa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the cognitive abilities and learning interests of students through the Contextual Teaching and Learning (CTL) learning model on Alternative Energy material for class X of SMA Muhammadiyah Limboro, West Seram. In this study, the subjects of the study were all students of class X IPA of SMA Muhammadiyah Limboro.The data of this study were collected through test and non-test instruments, test instruments in the form of tests and non-tests, test instruments in the form of initial tests and final tests, while non-test instruments in the form of Student Worksheets (LKPD) and student interest questionnaires. The results of the study showed that in the initial test, the average initial ability of students before using the Contextual Teaching and Learning (CTL) learning model had an average value of 34.7, which was in the failing qualification. The results of the analysis during the learning process showed an average student achievement score of 78.78, which was in the good qualification. The data on the average final ability of students after using the Contextual Teaching and Learning model had an average value of 77, which was in the good qualification. The student interest questionnaire for physics subjects using the Contextual Teaching and Learning learning model reached a very good qualification of 86.4.